Character Education for Islamic Boarding School Students through the Living Qur'an Approach Based on Technology Integration - Harahap, Muhammad Yunan (Sekolah Tinggi Agam Islam Sumatera Medan, 2025)
Islamic boarding schools in this era of transformation are required to maintain traditional values while adapting to technological developments. This condition encourages the need for educational innovation that not only emphasizes memorization but also the internalization of moral values based on the Qur'an. The Living Qur'an approach is relevant because it emphasizes the appreciation and practice of Qur'anic values in the lives of students. This study analyzes the integration of technology in the application of Living Qur'an as a moral education strategy at the Tahfizil Qur'an Islamic Boarding School of the North Sumatra Islamic Center Foundation. The method used is descriptive qualitative through observation, in-depth interviews, and documentation studies. The results show that the use of digital media such as memorization applications, online platforms, and social media can increase the effectiveness of moral values internalization, strengthen spirituality, and motivate students to practice Qur'anic teachings. The integration of technology creates adaptive and contextual learning without losing the authenticity of the Islamic boarding school. This study recommends the development of policies and teacher training based on Islamic values to optimize the role of technology in moral education through the Living Qur'an approach.